The Effect of Giving Aloe Vera Gel on Collagen Growth in Wistar Rats (Rattus Norvegicus) with Exposure to Ultra Violet-B Light - Inola Fitria; Djamin Djamin; Buter Samin (International Journal of Health and Pharmaceutical (IJHP), 2023)
Exposure to UV rays can cause photochemical damage to the DNA of cells in the body, triggering cancer formation, especially skin cancer in humans. The skin may lose elasticity. Research is needed to ensure that currently, we are still looking for plants or foods that contain collagen, which can prevent wrinkles. This research is an original experiment carried out in a laboratory. Two types of variables play a role in this research: independent variables and dependent variables. In this experiment, aloe vera gel was used as an independent variable as a substitute for UVB light exposure. Collagen development, measured in mouse skin, is the dependent variable here. This study found that the standard control group had no collagen growth and was stable. This was because the typical control treatment was not exposed to UVB rays; hence, collagen formation was stable. The group administered 15% aloe vera extract gel had a more substantial effect on rat skin tissue collagen development after UVB light exposure than the 5% and 10% groups. This is because a higher dose of aloe vera extract includes more chemical components that promote mouse skin collagen formation.